A tale of the nail: post-traumatic brain abscess from impalement injury - Eyitayo Alabi; Afolashade Saka; Edward Jolayemi; Bamidele Adebayo; Okezie Obasi Kanu (Romanian Neurosurgery)
Impalement injuries to the head are rare but serious and potentially life-threatening. They comprise approximately 0.3% of all head injuries and require emergency surgical intervention. These injuries are mostly accidental however increasing cases arising from assault is being reported with often satisfactory outcomes.